2020
DOI: 10.1002/adom.202001298
|View full text |Cite
|
Sign up to set email alerts
|

Thin‐Metal‐Film‐Based Transparent Conductors: Material Preparation, Optical Design, and Device Applications

Abstract: Transparent conductors are essential elements in an array of optoelectronic devices. The most commonly used transparent conductor – indium tin oxide (ITO) suffers from issues including poor mechanical flexibility, rising cost, and the need for annealing to achieve high conductivity. Consequently, there has been intensive research effort in developing ITO‐free transparent conductors over the recent years. This article gives a comprehensive review on the development of an important ITO‐free transparent conductor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 320 publications
(388 reference statements)
3
95
0
Order By: Relevance
“…Ge, Cu, and Al seed layers were compared on the basis of film roughness, binding strength energy, electrical resistivity, transmittance ( T ) of Ag films on these layers, and film stability, where the best performance was observed with a 5-Å Cu seed layer (see section S3). The readers can refer to a recent review article on thin metal film–based transparent conductors ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ge, Cu, and Al seed layers were compared on the basis of film roughness, binding strength energy, electrical resistivity, transmittance ( T ) of Ag films on these layers, and film stability, where the best performance was observed with a 5-Å Cu seed layer (see section S3). The readers can refer to a recent review article on thin metal film–based transparent conductors ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous works showed that the ultrathin Ag alloy is highly flexible and can even enhance outcoupling efficiency of OLEDs by suppressing waveguide mode formation (4,5). Ag alloy with two adjacent dielectric layers, called dielectric-metal-dielectric (DMD) electrode, is more widely used in many applications since DMD forms ultrasmooth surface and is compatible with the conventional OLED structure and fabrication processes (6)(7)(8).…”
Section: Objective and Backgroundmentioning
confidence: 99%
“…The rapid advances in flexible and wearable optoelectronic devices, such as light‐emitting diodes, photovoltaic cells, electrochromic devices, and transparent heating devices, necessitate the development of high‐performance transparent conductive electrodes (TCEs). [ 1–9 ] The critical requirements for TCEs are high visible transparency, electrical conductivity (typically represented as sheet resistance), and sufficient flexibility. Currently, the most commonly used material for TCEs is indium tin oxide (ITO) which when prepared at elevated temperatures above 473 K can achieve a sheet resistance close to 10 Ωsq –1 and an average optical transmittance of 80–90% over the visible spectral range.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Therefore, a primary approach toward fabricating high‐performance OMO electrodes has been to achieve 2D‐like metallic growth at the minimum film thickness. [ 2,3 ] To this end, a variety of wetting inducers have been proposed, including trace amounts of gas additives incorporated during Ag layer deposition, [ 9,21 ] co‐sputtering metallic impurities during Ag layer deposition, [ 17 ] and introducing high‐surface‐energy seed layers [ 22 ] and polymer surfactants [ 16 ] prior to Ag deposition. While some of these approaches have achieved considerable success, the TCE performance, commonly quantified by the Haacke figure of merit (FOM = T 10 / R s ), [ 23 ] is still inferior to that of high‐quality ITO electrodes.…”
Section: Introductionmentioning
confidence: 99%